Beyond Survivor: The Reconstruction of Self Following Intimate Partner Violence - Cavilli, Simonetta (Curtin University, 2017)
This thesis describes the results of qualitative research analysing the narratives of Australian women who have endured intimate partner violence (IPV), their decimation of self and identity and their process of recovery. Extensive analysis identified determinants assisting with recovery and produced a conceptual schema delineating attainment of salubrity after abuse. IPV is an intense ordeal and convalescence can be an arduous process yet realisable. Results of the analysis includes recommendations to improve knowledge of IPV.